Traceable and accurate quantification of iron in seawater using isotope dilution calibration strategies by triple quadrupole ICP-MS/MS: Characterization measurements of iron in a candidate seawater CRM - An, Betul; Can, Suleyman Z.; Bakirdere, Sezgin (ELSEVIER, 2020)
Accurate quantification of iron is crucial for the characterization of a candidate seawater certified reference material. Isotope dilution mass spectrometry as a primary method is one of the option for this purpose. In this study, triethylamine (TEA) assisted Mg(OH)(2) co-precipitation is developed and combined with isotope dilution mass spectrometry for the characterization of candidate certified reference material, UME CRM 1206. The analytical protocol of co-precipitation was optimized to achieve reproducible yields of similar to 100% Fe with high salt rejection (residual salinity similar to 0.003%). Three calibration strategies, single, double and triple isotope dilution mass spectrometry (IDMS) coupled with co-precipitation were investigated in terms of metrological aspects. The determination of Fe was carried out by ICP-MS with tandem configuration (ICP-MS/MS) using NH3/He cell gas which was optimized for the minimum background equivalence concentration to be able to measure highly accurate Fe-56/Fe-57 ratio with the highest possible sensitivity. The background corrected typical procedural blank levels and limit of detection calculated based on three times the standard deviation of blanks were found as 9 ng/kg (0.16 nM) and 11 ng/kg (0.20 nM) for single IDMS, respectively. Trueness of the developed analytical methods has been demonstrated using CASS-6 and NMIA MX014 with complete and very precise recoveries. SI-traceable values with combined uncertainty (k = 2) were obtained for single, double and triple IDMS as (12.70 +/- 0.16) ng/g, (12.728 +/- 0.084) ng/g and (12.732 +/- 0.062) ng/g, respectively. The relative combined uncertainty for each approach was calculated as 0.64%, 0.33% and 0.24%, respectively.
Keywords: Isotope dilution mass spectrometry; Single dilution; Double dilution; Triple dilution; Seawater; Iron; Triethylamine; Mg(OH)(2) co-precipitation; PLASMA-MASS SPECTROMETRY; REDUCED GRAPHENE OXIDE; DETECTOR DEAD-TIME; VOLTAMMETRIC DETERMINATION; CHELATING RESIN; DISSOLVED IRON; METALS; FE; PRECONCENTRATION; ELEMENTS; Chemistry